The dendritic cell–T helper 17–macrophage axis controls cholangiocyte injury and disease progression in murine and human biliary atresia. Issue 1 (10th November 2016) - Lages, Celine S.; Simmons, Julia; Maddox, Avery; Jones, Keaton; Karns, Rebekah; Sheridan, Rachel; Shanmukhappa, Shiva Kumar; Mohanty, Sujit; Kofron, Matthew; Russo, Pierre; Wang, Yui‐Hsi; Chougnet, Claire; et al.
Abstract : Biliary atresia (BA) is a fibroinflammatory obstruction of the extrahepatic biliary tree in neonates. While intrahepatic bile duct proliferation is universal at diagnosis, bile duct paucity develops later. We hypothesized that polarized T helper lymphocyte responses orchestrate progression of intrahepatic biliary injury in this disease. Interleukin 17A (IL‐17A)‐green fluorescent protein, cluster of differentiation 11c (CD11c)/diphtheria toxin receptor, and IL‐17 receptor A −/− mice were used to examine T‐lymphocyte polarization, inflammatory leukocyte recruitment, and biliary injury in rhesus rotavirus–induced BA. Multiparameter flow cytometry and automated image analysis of immunostaining were applied to liver tissue samples from infants with BA. In the mouse model, activated CD4 + lymphocytes started to emerge in the liver on day 8 after viral challenge, while innate immune responses were waning. Plasma IL‐17A levels rose concomitantly with hepatic accumulation of T helper 17 lymphocytes and myeloid dendritic cells. Targeted depletion of CD11c + dendritic cells diminished hepatic IL‐17A production and ameliorated intrahepatic bile duct injury. Recombinant IL‐17A induced expression of chemokine (C‐C motif) ligand 2 in neonatal cholangiocytes in vitro, and blockade of the corresponding chemokine (C‐C motif) receptor 2 reduced recruitment of inflammatory macrophages to the liver in vivo . Genetic disruption of IL‐17A signaling was associated with down‐regulation of hepatic Ccl2/Ccr2 messenger RNA expression, reduced infiltration of the liver with inflammatory Ly6C hi macrophages, and improved survival. In the liver of infants with BA, cholangiocytes were found to express IL‐17 receptor A, and the prevalence of IL‐17A + cells was positively correlated with the degree of CD68 + macrophage infiltration at diagnosis. Hepatic CD4 + lymphocytes were chief producers of IL‐17A in patients with progressive disease undergoing liver transplantation. Conclusion : These findings identify the dendritic cell–T helper 17–macrophage axis as a target for the development of strategies to block progression of intrahepatic bile duct injury in patients with BA. (Hepatology 2017;65:174‐188).